Craniosynostosis - Ramesh Kumar Sharma (Indian Journal of Plastic Surgery)
Craniosynostosis is a premature pathologic fusion of one or more cranial vault sutures that leads to abnormal shape of the skull. The fused sutures lead to restricted growth in some areas and compensatory bossing in other areas. The head may assume different shapes depending upon the site and timing of the abnormally fused suture. The exact cause of this suture pathology is still unknown, but the local dura, cranial base and the fibroblast growth factors seem to influence this. The diagnosis rests on clinical examination and confirmation is generally on the computed tomography scan. The need for surgery is both for cosmetic and functional reasons. Many cases may be associated with raised intracranial pressure with its attendant deleterious effects on vision and brain. The aim of treatment is to increase the cranial volume and reshape the skull. The surgery can be safely undertaken around 9-12 months in most of the cases. The conventional management is through an open surgical approach; although, some centres have claimed impressive results with limited endoscopic techniques in selected cases. The review article deals with the aetiopathogenesis, clinical presentations and management of the common varieties of craniosynostoses seen in the Indian scenario.